Assessment of Protective Potentials of Ficus Exasperata Leaf on Arsenate-Mediated Dyslipidemia and Oxidative Damage in Rat’s Brain (Journal of Basic and Applied Research in Biomedicine, 2022)
This study investigated the protective potentials of methanolic leaf extract of Ficus exasperata on sodium arsenate-mediated dyslipidemia and oxidative damage in the brain of rats. Twenty-eight rats were sorted into four groups containing seven rats each. Group A (control) received distilled water while 10 mg/kg bw of arsenic in form of sodium arsenate (As) was administered intraperitoneally to groups B, C and D. Group C and D were treated with oral administration of 100 mg/kg bw and 200 mg/kg bw of F. exasperata leaf respectively for 14 days. Arsenate administration resulted in dyslipidemia as shown by significant elevation (P